PEMULUNG ANAK DI TPA MUARA FAJAR KECAMATAN RUMBAI KOTA PEKANBARU - Vivi Listya Fitri; Hesti Asriwandari (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
TPA Muara Fajar is the only one landfill in Pekanbaru city which is an economic area for scavengers. Not just adult scavengers, but child scavenger so many found in the region. Standart Operation Procedure (SOP) TPA Muara Fajar forbid childrens to scavenge in TPA area, but they are breaking. This research aims to see activity and division of time works, study and playing of child scavenger, and their motivations scavenge in TPAMuara Fajar. Research methods used is descriptive qualitative. The result is in addition to scavenging they are also a student in formal school. They scavenge every day during the day until night. They do not have free time to play because studying in the school and full works in TPA. Their motivation to work as a scavenger is internal motivation that comes from self, and eksternal motivation from others and the environment of parents and peers who are also scavengers.Keywords: child scavenger, internal motivation, eksternal motivation, family